Interactions of the bovine placental lactogen and prolactin receptor genes are associated with fertility traits in cattle - W. Huang (Animal, 2009)
Decline in fertility of high-producing dairy cattle has become a global challenge to the dairy industry. Because of low heritability and complexity, it is difficult to find genetic markers for fertility traits in cattle. Here, we report the use of an in vitro fertilization (IVF) system and candidate gene approach to test genetic associations of a single-nucleotide polymorphism (SNP) in bovine placental lactogen (bPL), and its interactions with SNPs in the prolactin receptor (PRLR) and growth hormone receptor genes with fertility traits in an IVF system. The associations suggest a possible involvement of genetic interactions between bPL and PRLR in the fertilization and embryonic development processes, and the potential for application in a marker-assisted selection program.